Effects of fermentation and de-bittering methods on production of almond-like rambutan seed (Nephelium lappaceum L.) snack - Mehdizadeh, Shabnam (2014)
There are so many current studies going on in the field of waste products. One of the instances is seeds of rambutan, which is discarded yearly because of its slightly bitter taste despite the fact that it contains valuable source of oleic acid, arachidic acid and vitamins. The first part of this study determined the effect of fermentation on variability of fermentation index, polyphenol constituents and amino acids of rambutan seeds (anak sekolah). Results of fermentation showed that time of fermentation had a significant decrease in pH, whereas a significant increase was evident in the fermentation index (p<0.05). Findings also showed that microbial activities in the pulp produce alcohols to some extent and acids such as acetic acid and lactic acid, and raises the temperature and humidity and these changes inside the seed resulted in the death of the embryo. Moreover, it was found that fermentation significantly reduced the levels of total polyphenols (59%), tannin (60%) and saponins (33%). However, fermentation appeared to have a moderate effect on geraniin, corilagin and much stronger effect on ellagic and gallic acids. During fermentation, variability in gallic acid, geraniin, corilagin and ellagic acid did not show consistent trend. In contrast, amino acids that elicited bitter taste (phenylalanine, tyrosine and leucine) showed reduction of 20%, 30% and 40% respectively after 10 days of fermentation. Furthermore, it was discovered that sucrose, which was the only sugar present in significant amount, in unfermented seed was remarkably reduced during fermentation. The second part of this study concentrated on the effect of different debittering methods on the seed of rambutan. There were 14 different methods for reducing bitterness with different times and concentrations and in different soaking medium such as soaking in water and debittering through impregnation processes by sugar and salt as well as lye treatment. Three methods were selected based on the substantial reduction of bitterness compounds. These three methods were soaking in water for 7 days, treatment of seeds with 22% sodium chloride for 8 h and treatment of seeds with 1 N NaOH for 8 h, accordingly. The three most efficient methods indicated that tannin content declined by 55.4%, 48.2% and 40.9%. Similarly, polyphenol contentswere reduced to 92.7%, 84.4% and 85.1%. Saponin, gallic acid and corilagin, which are known as the prime causes of bitterness, were completely removed by these different treatments. However, geraniin was reduced by 20% during debittering methods. Tyrosine, leucine and phenylalanine were the three amino acids, which contain bitter taste in rambutan seeds were also reduced by the different debittering methods. The third part of this study focused on the effect of roasting on the texture, color and flavor of debittered seeds of rambutan and almond. Debittered rambutan seeds and almonds were roasted at 125 °C for 15 minutes, the volatile extract of rambutan seeds produced 13 odors and roasted almond produced 122 odors-active compounds by GC-MS. Findings showed that the highest peaks were associated to acids and ester groups. The results also showed that roasted debittered by 22% NaCl for 8 h and 7 days of soaking treatment were more similar to roasted almond than the other two treatments. In general, therefore, not only do the current findings add to a growing body of literature on the different debittering methods of rambutan seed, but also some efficient approaches were identified for debittering rambutan seed in which this may contribute significantly to produce a new almond-like snack.